2018
DOI: 10.3389/fphys.2018.01134
|View full text |Cite
|
Sign up to set email alerts
|

Where to Step? Contributions of Stance Leg Muscle Spindle Afference to Planning of Mediolateral Foot Placement for Balance Control in Young and Old Adults

Abstract: Stable gait requires active control of the mediolateral (ML) kinematics of the body center of mass (CoM) and the base of support (BoS) in relation to each other. Stance leg hip abductor (HA) muscle spindle afference may be used to guide contralateral swing foot placement and adequately position the BoS in relation to the CoM. We studied the role of HA spindle afference in control of ML gait stability in young and older adults by means of muscle vibration. Healthy young (n = 12) and older (age > 65 years, n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
108
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(119 citation statements)
references
References 41 publications
11
108
0
Order By: Relevance
“…In order to further explore these unanticipated increases in variability, a post hoc analysis of the relationship between COM and foot placement in the ML direction was performed. Based on the method of Wang and Srinivasan (2014), models to predict the lateral placement of the (dominant) swing foot based on ML COM state (excursion and velocity) during the preceding midstance were developed [for detailed methods, refer to Wang and Srinivasan (2014), noting that in the present study whole-body COM was employed instead of pelvis, as per Arvin et al (2018)]. Lateral step placement (analogous to step width in the present study) could be predicted by ML COM dynamics at the preceding midstance by the following equations, each based on 100 strides from each participant, with variables expressed as a deviation from the mean and coefficients averaged across the group: Greater excursion and velocity towards the swing foot was associated with a more lateral foot placement, and the relationship was maintained on both flat and uneven terrain.…”
Section: Discussion Initial Phase Of Walking On Uneven Terrain: Cautimentioning
confidence: 99%
See 2 more Smart Citations
“…In order to further explore these unanticipated increases in variability, a post hoc analysis of the relationship between COM and foot placement in the ML direction was performed. Based on the method of Wang and Srinivasan (2014), models to predict the lateral placement of the (dominant) swing foot based on ML COM state (excursion and velocity) during the preceding midstance were developed [for detailed methods, refer to Wang and Srinivasan (2014), noting that in the present study whole-body COM was employed instead of pelvis, as per Arvin et al (2018)]. Lateral step placement (analogous to step width in the present study) could be predicted by ML COM dynamics at the preceding midstance by the following equations, each based on 100 strides from each participant, with variables expressed as a deviation from the mean and coefficients averaged across the group: Greater excursion and velocity towards the swing foot was associated with a more lateral foot placement, and the relationship was maintained on both flat and uneven terrain.…”
Section: Discussion Initial Phase Of Walking On Uneven Terrain: Cautimentioning
confidence: 99%
“…Foot placement during unperturbed gait has been shown to be closely attuned to movement of the COM, as estimated from the pelvis or trunk (Arvin et al, 2016(Arvin et al, , 2018Roden-Reynolds et al, 2015;Wang and Srinivasan, 2014). Lateral foot positioning, for example, can be predicted from the velocity and position of the pelvis or whole-body COM (Arvin et al, 2018;Wang and Srinivasan, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Seethapathi and Sirinivasan [8] reported that ML foot Manuscript to be reviewed movements to movements of the upper body. Although the results of current study cannot answer the question whether active control or passive coupling is the underlying cause of this correlation, active control of ML stability through foot placement is supported by studies on the effects of sensory illusions induced by vibration [17], or visual perturbations [18] on this correlation, and by studies that have related ML foot placement to swing phase muscle activity [19]. On the other hand, we cannot rule out that the passive dynamics play a role in the correlation between ML trunk CoM state and subsequent ML foot placement that we report.…”
Section: Discussionmentioning
confidence: 58%
“…The R 2 (i.e. the ratio of predicted foot placement variance to actual foot placement variance) has been reported as the primary outcome in previous studies [17,14,16]. Manuscript to be reviewed placement [14,16].…”
Section: Experimental Set-upmentioning
confidence: 99%